Penyelesaian Peraturan Daerah Bermasalah Berdasarkan Asas Peraturan Perundang-Undangan - Aritonang, Syofina Dwi Putri; Nugroho, Ahmad; Syahrani, Nabila; Susmayanti, Riana (Universitas Jember, 2024)
Article 18 of the 1945 Constitution of the Republic of Indonesia stipulates that regional governments can carry out their government affairs based on the principles of autonomy and assistance duties. Regional regulations must be formed appropriately to reflect the needs of society and what needs to be regulated and resolved. So regional regulations must be in line with the guidelines on the principles of statutory regulations. However, as KPPOD data states, up to 2021 there are at least 347 regional regulations that are still problematic. For example, Surakarta City Regional Regulation Number 4 of 2011 concerning Regional Taxes, Mukomuko Regency Regional Regulation Number 5 of 2016 concerning Muslim and Muslim Dress for Students, and Bogor City Regional Regulation Number 10 of 2018 concerning Non-Smoking Areas. The research uses normative juridical research methods with a statutory and regulatory approach, with primary and secondary legal materials. The technique for collecting legal materials in this research was carried out using documentation studies. The research results show that the regional regulations that the author used as a case study in this research have problems in their implementation. These problems include conflicts of norms and regional regulations that differ in substance from the latest decisions testing the regulations used as guidelines by these regional regulations, which ultimately results in the emergence of legal uncertainty in society. Therefore, the competent authorities can immediately revise or revoke these regulations. Keywords: Principles of Statutory Regulations, Regional Government, Regional Regulations.